2019
DOI: 10.1037/drm0000103
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares in mental disorders: A review.

Abstract: No review has specifically focused on the experience of nightmares in individuals with a mental disorder. With a better understanding of nightmares in this population, clinicians will be more inclined to investigate for the presence of chronic nightmares, to consider nightmares for prognosis, and to treat this sleep difficulty independently from other mental disorders. Therefore, this narrative review aims to summarize the most relevant literature on the experience of nightmares in posttraumatic stress disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 134 publications
(197 reference statements)
2
26
0
1
Order By: Relevance
“…First, DD frequency is associated with other sleep-related problems including insomnia, sleepwalking, bruxism, sleep talking, sleep terrors, nighttime awakenings, and unwillingness to go to bed ( 29 37 ). Second, DDs have also been linked to a range of specific mental health symptoms and psychosocial problems, including low prosociality ( 37 , 38 ), academic problems ( 33 ), emotional excitability and being easily emotionally hurt ( 39 ), emotional symptoms ( 37 , 38 , 40 ), psychotic experiences ( 41 , 42 ), borderline personality disorder ( 40 ), other mental health disorders ( 43 ), as well as suicidal ideation and suicide attempts ( 44 46 ). A prospective study found that DD frequency at 12 years of age was related to symptoms of psychosis during adulthood ( 47 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, DD frequency is associated with other sleep-related problems including insomnia, sleepwalking, bruxism, sleep talking, sleep terrors, nighttime awakenings, and unwillingness to go to bed ( 29 37 ). Second, DDs have also been linked to a range of specific mental health symptoms and psychosocial problems, including low prosociality ( 37 , 38 ), academic problems ( 33 ), emotional excitability and being easily emotionally hurt ( 39 ), emotional symptoms ( 37 , 38 , 40 ), psychotic experiences ( 41 , 42 ), borderline personality disorder ( 40 ), other mental health disorders ( 43 ), as well as suicidal ideation and suicide attempts ( 44 46 ). A prospective study found that DD frequency at 12 years of age was related to symptoms of psychosis during adulthood ( 47 ).…”
Section: Introductionmentioning
confidence: 99%
“…In one narrative review by Lemyre et al [37], nightmare frequency was reported to be positively related to psychiatric outcomes such as posttraumatic stress, depressive, bipolar, anxiety and obsessive compulsive disorders, but not in ASD where they report the association between nightmares and psychometric outcomes is less clear. In this narrative review, adults with ASD were reported to have significantly fewer nightmares than controls and there appeared to be no relationship between ASD and nightmares in children and adolescents [37]. Inconsistent to previously reported data on nightmares in children with ASD, our study reports that children with ASD experienced a significantly higher number of nightmares than their TD peers.…”
Section: Nightmare Frequency and Psychometric Associationsmentioning
confidence: 99%
“…However the phenotypic presentation of nightmares in this population is less clear. Adults with ASD are reported to experience fewer nightmares than controls [37] whilst in paediatric ASD populations the incidence of parasomnias is higher [29], but nightmare frequency is variable in comparison to controls [37], with one study by Chou and colleagues [38] assessing 345 children with ASD, controls and siblings finding that siblings were more likely to experience nightmares than controls or the clinical population [38].…”
Section: Introductionmentioning
confidence: 99%
“…However, the phenotypic presentation of nightmares in this population is less clear. Adults with ASD are reported to experience fewer nightmares than controls [ 37 ], whilst in paediatric ASD populations the incidence of parasomnias is higher [ 29 ] but nightmare frequency is variable in comparison to controls [ 37 ]. One study with 345 children with ASD, controls and siblings demonstrated that siblings were more likely to experience nightmares than controls or the clinical population [ 38 ].…”
Section: Introductionmentioning
confidence: 99%